Chapter 6 Recovering mothers' experiences of HIV/ AIDS health activism in Edinburgh, 1983- 2000 - Elizabeth, Hannah J. (Manchester University Press, 2022)
Edinburgh was disproportionately affected by HIV/AIDS in the early 1980-1990s, and women and children were affected in higher numbers there than elsewhere in the UK. Edinburgh's AIDS crisis also followed a different pattern, with new infections predominantly occurring among IV drug users and heterosexuals. Because of the high rates of HIV infection among women in Edinburgh, the city rapidly became host to numerous charities and organisations scrambling to meet the needs of HIV-affected women and families, aiming to prevent new infections and meet the emotional, medical, housing, and educational needs of those already affected by the virus. This chapter traces how healthcare workers and HIV-affected women responded in Edinburgh. This was interdisciplinary collaborative AIDS activism born out of the daily fight for resources, information, space, and empathetic treatment for women and their families. This activism can be traced in texts both academic and creative, and was at the very least a backdrop for many women's experience of HIV and AIDS in Edinburgh in the late twentieth century. To focus the analysis, the creation of the Paediatric AIDS Resource Centre (PARC) in Edinburgh is examined, alongside some of the items the centre published. The need for PARC is demonstrated not just by placing it in its social, political, and historical context, but by recovering the words of HIV-affected women and healthcare workers drawing on its resources, writing these women back into the history they created as subjects rather than objects.